Anderson-Mott transition in a disordered Hubbard chain with correlated hopping - Battista, Francesca (2017)
We study the ground-state phase diagram of the Anderson-Hubbard model with correlated hopping at half-filling in one dimension. The Hamiltonian has a local Coulomb repulsion U and a disorder potential with local energies randomly distributed in the interval (-W,+W) with equal probability, acting on the singly occupied sites. The hopping process which modifies the number of doubly occupied sites is forbidden. The hopping between nearest-neighbor singly occupied and empty sites or between singly occupied and doubly occupied sites has the same amplitude t. We identify three different phases as functions of the disorder amplitude W and Coulomb interaction strength U>0. When U<4t the system shows a metallic phase: (i) only when no disorder is present W=0 or an Anderson-localized phase, (ii) when disorder is introduced W≠0. When U>4t the Anderson-localized phase survives as long as disorder effects dominate on the interaction effects, otherwise a Mott-insulator phase (iii) arises. Phases (i) and (ii) are characterized by a finite density of doublons and a vanishing charge gap among the ground state and the excited states. Phase (iii) is characterized by the vanishing density of doublons and a finite gap for the charge excitations.